ENGLISH LANGUAGE TRAINING FOR ISLAMIC SCHOOLS (ELTIS): TRAINEES' OUTLOOK - Zuliati Rohmah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
This study reports on an internal evaluation of an in service training in Indonesia called English Language Training for Islamic Schools (ELTIS). The data obtained from questionnaires were cross-referenced through document reviews and focus group discussions. A total of 187 Islamic junior high school teachers respond- ed to the questionnaire. The questionnaire asked about any improvements they expe- rienced, the support from their schools to apply the new knowledge and skills, and the relevance of the training to their needs. The results showed that the English abili- ty and the teaching skills of the teachers had improved. Support from the schools was found to be very high, although parental support was not as high as expected. ELTIS materials were generally found to meet needs of madrasahs, but were not re- ally appropriate for the Islamic context. Interestingly, the teachers stated that the ma- terials would be used in their schools after the closure of ELTIS